1998
DOI: 10.1021/ma971459p
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical Control of Internal Superstructure, Diameter, and Stability of Supramolecular and Macromolecular Columns Generated from Tapered Monodendritic Building Blocks

Abstract: The synthesis of the first generation AB 3 monodendrons 3,4,5-tris[6-alkyloxy-2-methylnaphthyloxy]benzoic acid (with decyl, dodecyl, tetradecyl, and hexadecyl alkyl groups), 3,4,5-tris[4-(4′dodecyloxyphenyl)benzyloxy]benzoic acid, their ω-hydroxy(tetraethylene glycol) esters, and the corresponding methacrylates and poly(methacrylate)s is described. All monodendrons and the corresponding polymers self-assemble into supramolecular columns that self-organize in a columnar hexagonal (Φh) thermotropic liquid crysta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
87
1

Year Published

1999
1999
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(92 citation statements)
references
References 16 publications
4
87
1
Order By: Relevance
“…[2a, 6,12,13] The electron density computed from the XRD data is consistent with both the pyramidic and nonhelical pine-tree models for the packing of the dendritic molecule (3,4,5) 2 12F8G2-CO 2 CH 3 in the columnar LC phase.…”
supporting
confidence: 64%
“…[2a, 6,12,13] The electron density computed from the XRD data is consistent with both the pyramidic and nonhelical pine-tree models for the packing of the dendritic molecule (3,4,5) 2 12F8G2-CO 2 CH 3 in the columnar LC phase.…”
supporting
confidence: 64%
“…7 Limited availability of AB n monomers increases the use of readily available A 2 þ B 3 monomers for the synthesis of HBP. 8,[9][10][11] After preliminary work by Kim 12 on hyperbranched liquid crystalline polymers, (HBLCPs), synthesized by the AB n approach, the revolutionary work in this field was carried out by Percec et al, [13][14][15][16][17][18] Shibaev et al, 19 and others [20][21][22][23] have reported on photo-addressable dendritic polymers (PADLCPs) containing both mesogenic and photochromic groups. PADLCPs have shown enhanced physicochemical properties and photo and thermally induced physical changes as compared with linear polymers.…”
Section: Introductionmentioning
confidence: 99%
“…These three new building blocks, together with 4-[4'-(ndodecan-1-yloxy)phenyl]benzyl chloride (11), prepared as previously reported, [26] were employed in the synthesis of seven libraries of dendrons. The synthesis of the dendrons was accomplished by using the convergent strategy [2] developed in our laboratory for the synthesis of dendritic benzyl ethers.…”
Section: Resultsmentioning
confidence: 99%
“…The synthesis of (4'-(n-dodecane-1-yloxy)biphenyl-4-methyl chloride (17) was performed as reported previously. [26] Pyridinium hydrochloride was prepared by the dropwise addition of HCl to pyridine until pH 4-5 was reached, followed by evaporation of water.…”
Section: Synthesismentioning
confidence: 99%